2020
DOI: 10.1002/rra.3572
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and anthropogenic impacts on water and sediment generation in the middle reach of the Jinsha River Basin

Abstract: Response of water and sediment generation to climate change and anthropogenic activities is becoming a hot topic in the middle reach of the Jinsha River Basin. In this research, coefficients of variation and concentration degree (i.e., Cv and Cd) and double mass curve (DDC) were adopted to examine the changes in water and sediment discharge and their relationships with precipitation. The contribution rates of climatic and anthropogenic factors to water and sediment discharge were assessed through comparisons b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[5,6], with precipitation being the crucial driving factor [7]. In addition, with rapid economic development, human activities are altering the ecological environment of a basin in the form of greenhouse gas emissions, land-use changes, water conservancy construction, and human water consumption, resulting in an increasingly significant effect on river runoff [8,9]. Therefore, evaluating the influence of climate change and human activities on river runoff is meaningful for rational water resources management, protecting ecological balance, and maintaining sustainable socio-economic development [10].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6], with precipitation being the crucial driving factor [7]. In addition, with rapid economic development, human activities are altering the ecological environment of a basin in the form of greenhouse gas emissions, land-use changes, water conservancy construction, and human water consumption, resulting in an increasingly significant effect on river runoff [8,9]. Therefore, evaluating the influence of climate change and human activities on river runoff is meaningful for rational water resources management, protecting ecological balance, and maintaining sustainable socio-economic development [10].…”
Section: Introductionmentioning
confidence: 99%
“…Trends within climatic variable time series have received considerable attention in recent decades [10] and have been investigated using different methodologies, including parametric and/or nonparametric procedures, such as the Mann-Kendall (MK) test [11][12][13], linear regression method [6,14], while the increasing trend during spring was more significant than those during the other seasons. Various other studies [38][39][40] have also applied the MK approach to investigate trends in climatic variables such as temperature and precipitation in the JRB. However, a limited number of studies have focused on spatial and temporal variations in different categories of temperature and precipitation, especially for the low and high categories.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, Santucci et al (2005) found little evidence of the cumulative effects of low-head dams (< 15 m in height). There are few existing studies that compare the effects of single versus multiple dams on the hydrologic regime (Zhao et al, 2012). Are the effects of multiple dams additive, multiplicative or largely insignificant?…”
Section: Introductionmentioning
confidence: 99%